Роль метаболических нарушений в формировании когнитивной дисфункции при сахарном диабете 2 типа = Role of metabolic disorders in the formation of cognitive dysfunction in type 2 diabetes mellitus - Tovazhnyanska, O. L.; Bezuglova, I. O. (Journal of Education, Health and Sport, 2016)
Tovazhnyanska O. L., Bezuglova I. O. Роль метаболических нарушений в формировании когнитивной дисфункции при сахарном диабете 2 типа = Role of metabolic disorders in the formation of cognitive dysfunction in type 2 diabetes mellitus. Journal of Education, Health and Sport. 2016;6(8):284-295. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.60585 http://ojs.ukw.edu.pl/index.php/johs/article/view/3759 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.08.2016. Revised 08.08.2016. Accepted: 19.08.2016. РОЛЬ МЕТАБОЛИЧЕСКИХ НАРУШЕНИЙ В ФОРМИРОВАНИИ КОГНИТИВНОЙ ДИСФУНКЦИИ ПРИ САХАРНОМ ДИАБЕТЕ 2 ТИПА Е. Л. Товажнянская, И. О. Безуглова Харьковский национальный медицинский университет Резюме Изучено состояние метаболических процессов у 107 больных с сахарным диабетом 2 типа, диабетической энцефалопатией и когнитивными нарушениями и у 40 пациентов с сахарным диабетом 2 типа без клинически значимых изменений нервной системы. Когнитивные нарушения у пациентов с СД 2 типа характеризовались снижением общего балла когнитивной продуктивности, значимым снижением памяти, беглости речи, внимания и ориентации. Нарушение липидтранспортной и оксидантно-антиоксидантной систем у больных с СД 2 типа проявлялось накоплением атерогенных фракций липопротеидов и прооксидантов в сочетании с достоверным снижением содержания антиатерогенных и антиоксидантных факторов. Корреляционный анализ выявил, что дислипидемия и оксидантно-антиоксидантный дисбаланс при СД 2 являются важными факторами развития и прогрессирования когнитивной дисфункции у больных сахарным диабетом 2 типа. Ключевые слова: сахарный диабет 2 типа, диабетическая энцефалопатия, когнитивные нарушения, липидная система, оксидантно-антиоксидантная система. ROLE OF METABOLIC DISORDERS IN THE FORMATION OF COGNITIVE DYSFUNCTION IN TYPE 2 DIABETES MELLITUS O. L. Tovazhnyanska, I. O. Bezuglova Kharkiv National Medical University Summary The state of metabolic processes in 107 patients with type 2 diabetes mellitus, diabetic encephalopathy and cognitive impairment and in 40 patients with type 2 diabetes without clinically significant changes in the nervous system was studied. Cognitive impairment in patients with type 2 diabetes were characterized by a decrease in the total score of cognitive productivity, a significant reduction in memory, speech fluency, attention and orientation. Violation of lipid and oxidant-antioxidant systems in patients with type 2 diabetes were accompanied by the accumulation of atherogenic lipoproteins and pro-oxidants, combined with a reduction of anti-atherogenic and antioxidant factors. Dyslipidemia and oxidant-antioxidant imbalance are important factors in the development and progression of cognitive dysfunction in patients with type 2 diabetes that was proved by correlation analysis. Key words: type 2 diabetes mellitus, diabetic encephalopathy, cognitive impairment, the lipid system, the oxidant-antioxidant system. РОЛЬ МЕТАБОЛІЧНИХ ПОРУШЕНЬ У ФОРМУВАННІ КОГНІТИВНОЇ ДИСФУНКЦІЇ ПРИ ЦУКРОВОМУ ДІАБЕТІ 2 ТИПУ О. Л. Товажнянська, І. О. Безуглова Харківський національний медичний університет Резюме Вивчено стан метаболічних процесів у 107 хворих на цукровий діабет 2 типу з діабетичною енцефалопатією і когнітивними порушеннями й у 40 пацієнтів з цукровим діабетом 2 типу без клінічно значущих змін нервової системи. Когнітивні порушення у пацієнтів з ЦД 2 типу характеризувалися зниженням загального бала когнітивної продуктивності, значущим зниженням пам'яті, швидкості мови, уваги і орієнтації. Порушення ліпідтранспортної й оксидантно-антиоксидантної систем у хворих на ЦД 2 типу виявлялись у вигляді накопичення атерогенних фракцій ліпопротеїдів та прооксидантів у поєднанні з достовірним зниженням вмісту антиатерогенних і антиоксидантних факторів. Кореляційний аналіз виявив, що дисліпідемія і оксидантно-антиоксидантний дисбаланс при СД 2 типу є важливими факторомами розвитку і прогресування когнітивної дисфункції у хворих на цукровий діабет 2 типу. Ключові слова: цукровий діабет 2 типу, діабетична енцефалопатія, когнітивні порушення, ліпідна система, оксидантно-антиоксидантна система.